Study on the Bioactive Properties of Polyetheretherketone - Pan, Yusong; Xu, Chuyang; Pan, Chengling (Asian Journal of Chemistry, 2013)
Polyetheretherketone has been increasingly employed as biomaterials due to its excellent biological characteristics. In this paper, the bioactivity of polyetheretherketone was investigated. The results showed that the bioactivity of polyetheretherketone could be improved by various techniques such as plasma treatment, surface grafting, surface deposition and addition of bioactive glass ceramic in the polyetheretherketone matrix. The aim of plasma treatment is to change the surface physicochemical properties of polyetheretherketone, thus enhancement the surface bioactivity of polyetheretherketone composites. Surface coating technique is devoted to improve the bioactivity of polyetheretherketone by deposition of bioactive ceramics such as hydroxyapatite and calcium phosphate on the surface of polyetheretherketone. Surface grafting modification is mainly attributed to improve the surface hydrophilicity and wettability through the grafting with hydrophilic or specific functional groups on the materials surface, thus enhancing bioactive performance of the material. The advantages of compounding bioactive glass ceramic with polyetheretherketone matrix are not only improving the bioactive properties but also increasing the mechanical properties of polyetheretherketone.